Application Of Openrisk At Open Cast Coal Mines - L. Munsamy; B. J. Madden (The Southern African Institute of Mining and Metallurgy, 2006)
OpenRisk, an open cast risk rating system, takes into account relative differences in the importance of hazards, as experienced on each mine as a result of different combinations of geotechnical factors and mining conditions. The system is based on critical geotechnical and operational parameters that have been identified by mining personnel and rock engineers. The primary advantage of this risk rating system is that all the strip mines would use an identical system, which enables the user to compare their risk to the risk at neighbouring mines and/or other open cast mines. The system can be adjusted to meet local, mine specific requirements. This system has been made practical and easy to use. Therefore, this tool can be used by personnel from other disciplines not directly related to rock engineering. OpenRisk system has been in operation at nine Anglo Coal and other open cast mines. It adequately detects areas of high risk and generates adequate remedial solutions to reduce the risks. Awareness of the personnel has been higher at the sites that use OpenRisk. The proactive approach of OpenRisk ensures that all personnel are aware of risks in the pits and how to deal with potential risky areas.